The inheritance and gift tax in Germany: Reform potentials for tax revenue, efficiency and distribution (Public Sector Economics - submission site, 2020)
The inheritance tax is often seen as an effective tool to reduce wealth inequality, raise public revenues if needed, and increase incentives to work by lowering the tax burden on labour, which is especially high in Germany, according to the OECD. The purpose of this paper is to shed light on the question of whether an inheritance tax is a promising tool for fighting wealth inequality without having distorting effects on the economy. For this purpose, firstly, the distributional effects of inheritances on wealth distribution are evaluated for Germany and are then compared with those in Austria and France, using data from the Household Finance and Consumption Survey (HFCS). A change in German inheritance tax law in 2009 is further used in a difference-in-difference analysis to identify the behavioural effects of the change in the inheritance tax on the volume of bequests, which are large and robust for different specifications.